1970
DOI: 10.1139/z70-060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fasting and exercise on lipid levels in muscle. A cytological and biochemical study

Abstract: Light and electron microscopic studies on the effect of fasting and exercise on lipids in the pectoralis muscle of the pigeon have revealed considerable increase in intracellular as well as extracellular lipids (1) in fasted pigeons and (2) in normal and fasted pigeons when the muscle of one side was electrically stimulated for different periods of time. Similar increase in lipids was also seen in the contralateral quiescent muscle. These observations were confirmed by bioehemical assays of the lipid content i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

1971
1971
1995
1995

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 0 publications
1
9
1
Order By: Relevance
“…In contrast to these results concerning interfascicular lipid, Vallyathan, Grinyer et al (1970) found an increase in the amount of "extracellular lipid" in the pectoralis muscle of the Common pigeon either as a result of starvation for 72 hours or as a result of electrical stimulation of the muscle. However, the extracellular lipid shown in their micrographs did not appear in discrete situations between muscle bundles, but was lying over the sectioned fibres.…”
Section: Diurnal Changescontrasting
confidence: 84%
See 1 more Smart Citation
“…In contrast to these results concerning interfascicular lipid, Vallyathan, Grinyer et al (1970) found an increase in the amount of "extracellular lipid" in the pectoralis muscle of the Common pigeon either as a result of starvation for 72 hours or as a result of electrical stimulation of the muscle. However, the extracellular lipid shown in their micrographs did not appear in discrete situations between muscle bundles, but was lying over the sectioned fibres.…”
Section: Diurnal Changescontrasting
confidence: 84%
“…Some workers have found that starvation or exercise causes a decrease in the intracellular lipid content (Bell, 1911;Parker & George, 1975a) and extractable lipid or triglyceride content (George & Jyoti, 1955;Carlson, 1967) of muscle. However, contrary to these findings, Masoro, Rowel1 et al, (1966) Denton & Randle (1967), Masoro (1967) and Vallyathan, Grinyer et al, (1970) observed an initial increase in the intracellular lipid content of muscle following starvation or exercise. A similar result is reported in this study for those individuals captured in 1976 ( Fig.…”
Section: Diurnal Changesmentioning
confidence: 87%
“…Both biochemical and histochemical studies hitherto carried out on energy metabolism during short-term and long-term muscular exercise in the pigeon, have shown that initially carbohydrate is utilized but in prolonged muscular activity, fat forms the chief fuel, thus sparing carbohydrate (GEORGE & BERGER, 1966;VALLYATHAN et al, 1970;JOHN & GEORGE, 1973;MCKEOWN et al, 1974;PARKER & GEORGE, 1974. In the present study, it was observed that, while the levels of blood glucose and liver glycogen were maintained more or less constant during prolonged muscular activity (5 h), accumulation of blood lactate was maintained at a constant level of approximately 35% over the control.…”
Section: Figures In Parentheses Denote Number Of Birds Usedmentioning
confidence: 99%
“…That in Birds fat is preferentially used as fuel during continuous flight and glycogen for short bursts of activity has been well documented (GEORGE & BERGER, 1966;VALLYATHAN et al, 1970; . Though the avian body is thus geared predominantly for aerobic metabolism and utilization of lipid as main fuel, it maintains a high blood.sugar level, two or three times higher than that of the mammalian (see BELL, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…Muscle fiber types, distinguished by their physiological biochemical, and histochemical characteristics, appear to differ not only in their predominantly glycolytic or oxidative metabolism, but also in their capacity to utilize lipids for energy [Vallyathan et al, 1970;Bealty and Bocek, 1970; Heiner and Domonkos, 1970;Essen et al, 19751.…”
Section: Ntro D U Ctlo Nmentioning
confidence: 99%